GAME-BASED ARABIC LEARNING AT MAN 2 BUKITTINGGI: BEST PRACTICE / BEST PRACTICE: PEMBELAJARAN BAHASA ARAB BERBASIS PERMAINAN DI MAN 2 BUKITTINGGI - Mailis Mailis (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
The research aims to explore the implementation of game-based learning to improve Arabic achievement of students at MAN 2 Bukittinggi. This was a descriptive qualitative research. Data were collected by doing observation and test. Game-based Arabic learning was implemented to 30 students of grade X of IPA 3 at MAN 2 Bukittinggi. Results showed that the procedures of game-based Arabic learning are: determine basic competence and indicators; motivate students, inform the learning purpose; prepare games based on themes; explain the game manual; demonstrate the game in front of the class; explain the learning materials; give chances to students to join the game; ask students to do tasks; correct students’ answers; give feedback and clarification about the learning process; and give reward to the active students. By applying the game-based Arabic learning, more than 75% students got high scores (above KKM). The game-based Arabic learning encourages the improvement of students’ thinking skills, attract students’ interest and motivation to learn, and also overcome boredom in learning. However, on the other side, applying game-based learning makes the class noisy and it is quite difficult to control the students’ activity.